A twister of twists, a tangler of tongues tongue twisters - Schwartz, Alvin 1927-; Rounds, Glen 1906- (Philadelphia Lippincott, 1972)
A collection of tongue twisters, both traditional and new in prose and verse.
Bibliography : p. 121-125.
Keywords: Tongue twisters; Nonsense verses; Tongue twisters